Clinical research and drug regulation in the challenging times of individualized therapies: A pivotal role of clinical pharmacology - Antonio Gómez-Outes; Aránzazu Sancho-López; Antonio J. Carcas Sansuan; Cristina Avendaño-Solá (Elsevier, 2024)
Since the 1980s, medical specialists in Clinical Pharmacology have been playing a crucial role in the development of drug regulation in Spain. In this article we report on the activities carried out and the prospects for development in three very relevant areas from the regulatory perspective: 1) the development of stable public infrastructures to facilitate non-commercial clinical research with medicines, 2) the regulatory aspects of individual access to medicines in special situations, beyond their regular access after marketing approval and funding by the National Health System, and 3) the challenges of development and access to advanced therapies, with special reference to the figure of the hospital exemption.